Single nucleotide polymorphisms and domain/splice variants modulate assembly and elastomeric properties of human elastin. Implications for tissue specificity and durability of elastic tissue. Issue 5 (May 2017) - Miao, Ming; Reichheld, Sean E.; Muiznieks, Lisa D.; Sitarz, Eva E.; Sharpe, Simon; Keeley, Fred W.
Abstract: Polymeric elastin provides the physiologically essential properties of extensibility and elastic recoil to large arteries, heart valves, lungs, skin and other tissues. Although the detailed relationship between sequence, structure and mechanical properties of elastin remains a matter of investigation, data from both the full‐length monomer, tropoelastin, and smaller elastin‐like polypeptides have demonstrated that variations in protein sequence can affect both polymeric assembly and tensile mechanical properties. Here we model known splice variants of human tropoelastin (hTE), assessing effects on shape, polymeric assembly and mechanical properties. Additionally we investigate effects of known single nucleotide polymorphisms in hTE, some of which have been associated with later‐onset loss of structural integrity of elastic tissues and others predicted to affect material properties of elastin matrices on the basis of their location in evolutionarily conserved sites in amniote tropoelastins. Results of these studies show that such sequence variations can significantly alter both the assembly of tropoelastin monomers into a polymeric network and the tensile mechanical properties of that network. Such variations could provide a temporal‐ or tissue‐specific means to customize material properties of elastic tissues to different functional requirements. Conversely, aberrant splicing inappropriate for a tissue or developmental stage or polymorphisms affecting polymeric assembly could compromise the functionality and durability of elastic tissues. To our knowledge, this is the first example of a study that assesses the consequences of known polymorphisms and domain/splice variants in tropoelastin on assembly and detailed elastomeric properties of polymeric elastin.